Analysis of heat exchanger equipped with various twisted turbulator inserts utilizing tripartite hybrid nanofluids - Kumar V.; Sahoo R.R. (My University, 2025)
This paper investigates the exergo-economic analysis of heat exchanger devices assisted with water-based different tripartite hybrid nanofluids (TPHNF) under various geometrical turbulator inserts modifications. Simulation is proceeded for tripartite hybrid nanofluids of mainly six various compositions based on the nanoparticles morphology variant and three different turbulators inserts at the core of plain tubes heat exchanger. Exergy, energy, environment and economy aspects with sustainability analysis of the device are studied with operating parameters. Investigation revealed that turbulator inserts with TPHNF result in a significant improvement in the performance of the device. The device inserts with DTTI in plain tubes using TPHNF 6 results in the highest 20.6% overall heat transfer coefficient, 18.1% exergy change, 2.74% exergy efficiency, 4.8% performance index, and higher sustainability index at low Reynolds number than without inserts; meanwhile, turbulator inserts yield to highest 47.8% operating cost and equivalent CO2 emissions. Result reveals that DTTI with TPHNF 6 should be preferred as working fluid as its PEC ranges highest 1.42–2.35, and THNF 2 working fluid should be least preferred due to its high operating cost. © 2022, Akadémiai Kiadó, Budapest, Hungary.